2019
DOI: 10.1111/jbi.13561
|View full text |Cite
|
Sign up to set email alerts
|

Identifying temporal and spatial patterns of diatom community change in the tropical Andes over the last c. 150 years

Abstract: Aim Lakes in the Ecuadorean Andes span different altitudinal and climatic regions, from inter Andean plateau to the high‐elevation páramo, which differ in their historical evolution in the several centuries since the pioneering Humboldt expeditions. Here, we evaluate temporal and spatial patterns of change in diatom assemblages between historical (palaeolimnological) and modern times. Location Ecuadorean Andes Methods We compared historical (pre‐1850) and modern (2017) diatom assemblages from 21 lakes and dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 69 publications
1
10
0
Order By: Relevance
“…In the Ecuadorian páramo, shallow lakes (< 8 m depth), such as Fondococha, are strongly influenced by energy transfer from the catchment (e.g., organic matter, floods, land use) (Giles et al 2018), whereas deeper lakes (e.g., Piñan, albeit cored in the shallow platform) respond more to local physical and chemical conditions in the water column (e.g., nutrients, thermal stratification) (Luethje 2020). We confirmed that Andean lake diatom communities are influenced by both local and regional factors (in agreement with Benito et al 2019); thus, the observed asynchrony is likely due to water chemistry differences mediated by lake‐specific flushing (Leavitt et al 2009).…”
Section: Discussionsupporting
confidence: 91%
“…In the Ecuadorian páramo, shallow lakes (< 8 m depth), such as Fondococha, are strongly influenced by energy transfer from the catchment (e.g., organic matter, floods, land use) (Giles et al 2018), whereas deeper lakes (e.g., Piñan, albeit cored in the shallow platform) respond more to local physical and chemical conditions in the water column (e.g., nutrients, thermal stratification) (Luethje 2020). We confirmed that Andean lake diatom communities are influenced by both local and regional factors (in agreement with Benito et al 2019); thus, the observed asynchrony is likely due to water chemistry differences mediated by lake‐specific flushing (Leavitt et al 2009).…”
Section: Discussionsupporting
confidence: 91%
“…The Cajas alkalinity range includes the two ecological thresholds (i.e., $ 200 and $ 1000 μeq L À1 ) identified in European mountain ranges in terms of community composition (Catalan et al 2009a). Diatoms and some crustaceans show this nonlinear community response to the alkalinity gradient, which will be interesting to confirm in this far-flung lake district, which shares with European ranges many diatom species (Benito et al 2019), but not crustaceans (Catalan and Donato-Rond on 2016).…”
Section: Ecological Implicationsmentioning
confidence: 73%
“…Currently, high‐mountain lakes across the globe are considered sentinels of the systemic change of the planet (Moser et al 2019). In this context, there is a growing interest in tropical high‐mountain lakes (Michelutti et al 2015; Van Colen et al 2017; Benito et al 2019; Steinitz‐Kannan et al 2020; Zapata et al 2021), which have historically received less attention (Eggermont et al 2007). Although high‐mountain lakes are among the most comparable ecosystems globally, and a common conceptual framework might be used to analyze them (Catalan and Donato‐Rondón 2016), tropical high‐mountain lake regions have unique environmental characteristics that require special attention.…”
mentioning
confidence: 99%
“…Biological assemblages accumulate with lake sediments as natural archives, which can be used to understand temporal dynamics of biodiversity and provide insights into the organization of ecological communities and their responses to natural and human-induced drivers (e.g., habitat loss, human impacts, eutrophication) (Willis et al, 2010;Heino et al, 2016). Because lakes are not isolated in the landscape (rather they form a continuum embedded in a terrestrial matrix), researchers have also examined the role of spatial variables in determining biodiversity patterns using paleolimnological approaches (Castillo-Escrivà et al, 2017;Benito et al, 2019). However, contemporary and paleolimnological studies still remain largely disconnected in biodiversity and environmental change research (Gregory-Eaves and Beisner, 2011).…”
Section: Introductionmentioning
confidence: 99%